Особливості гіперо-гіпонімічних відношень в англійських лексикографічних термінологічних словосполученнях - Гайволя, Оксана Леонідівна; Hayvolia, O. L. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті виділено види термінологічних словосполучень залежно від кількості одиниць, висвітлено пи¬тання сутності лексико-семантичної категорії гіпонімії, родо-видових відношень в англійських лексикографіч¬них термінологічних словосполученнях із погляду продуктивності, виділено найпродуктивніші родові еле¬менти, ядро, основну систему та периферію. Окрім того, визначено основні властивості та ознаки гіперонімів та гіпонімів, які відображать системність і цілісніть англійської лексикографічної багатокомпонентної терміно¬лексики, висвітлено специфіку їх семантики. The analysis of kind and type relations of the language units is important for organizing the lexical and terminological systems, lexicographical one, in our case. Such a type of relations is one of the fundamental for structuring of the language vocabulary. Terminological word-combinations reveal all the necessary peculiarities of the notion they designate. This article determines the types of terminological word-combinations according to the number of their components. The essence of lexico-grammatical category of hyponymy, kind and type relations in such word-combinations have been investigated from the point of view of their productivity. The most productive hyperonyms, the nuclear and the periphery have been determined in these multicomponent term-word-combinations. The main characteristics of hyperonyms and hyponyms which represent the system organization of the English lexicographical multicomponent terminology as well as their semantic features have been revealed. The results of the investigation have shown that kind and type relations reflect hierarchical organization of the terminological system of Lexicography.
The Peculiarities of Hyper-Hyponimic Relations in the English Lexicographic Terminological Word-Combinations
Keywords: гіперо-гіпонімічні відношення; hyper-hyponimic relations; гіперонім; hyperonym; гіпонім; hyponym